2012
DOI: 10.1177/0892705712439570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diisocyanates on the properties and morphology of epoxy/polyurethane interpenetrating polymer networks

Abstract: The present work investigates the effect of epoxy resin (EP) modification with polyurethanes (PURs) based on polyethylene glycol and two different diisocyanates: 4,4'-diphenylmethane diisocyanate (MDI) and 2,4-toluene diisocyanate (TDI). The impact strength of the material based on 15 wt% PUR with TDI was enhanced by 130%, while the critical stress intensity factor and the flexural strength of epoxy composition based on 5 wt% PUR with MDI increased by approximately 140% in comparison with unmodified EP. Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Epoxy resins (EPs) are well-known for their versatile applications covering coatings, adhesives and matrices of composites [1][2][3][4]. The widespread use EPs is mostly due to their good mechanical The synthesis of the DA adduct -see the above scheme-was performed similarly to those reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins (EPs) are well-known for their versatile applications covering coatings, adhesives and matrices of composites [1][2][3][4]. The widespread use EPs is mostly due to their good mechanical The synthesis of the DA adduct -see the above scheme-was performed similarly to those reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have revealed that blending of epoxy with poly(oxyethylene) (PEG 400)‐based polyurethane led to 60% improvement in the impact strength, while in a separate study introduction of polyurethane (40% w/w) reportedly increased the impact toughness by 46% . In comparison, the improvement in impact strength is larger (190%) when poly(oxypropylene)‐based polyurethanes are blended with epoxy.…”
Section: Resultsmentioning
confidence: 97%
“…In comparison, the improvement in impact strength is larger (190%) when poly(oxypropylene)‐based polyurethanes are blended with epoxy. Interestingly, blending of epoxy with polyester polyurethanes leads to larger improvements in impact strength (200%), as compared with polyether polyurethanes which may be attributed to the additional sites of hydrogen bonding available with the former. However, irrespective of the type of polyurethane being blended, the main cause behind the toughened nature of blends is the elastomeric nature of the polymer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations